Microstructural evolution and high strain rate mechanical property of cobalt superalloy contain titanium - Tao, Hsing Chen; Ting, You Chen (Universiti Kebangsaan Malaysia, 2015)
The high strain rate properties and microstructure observations of cobalt base superalloyd contains 0.9% Ti were investigated using Hopkinson bar. These cobalt base superalloys are tested at strain rates of 2×103, 3×103 and 4×103 s-1 and at different temperatures (25, 500 and 900°C), respectively. It is found that the stress flow and strain rate sensitivity increases with increasing strain rate but decrease with increasing temperature. The microstructure observations confirm that the high strain rate mechanical behavior of the cobalt base superalloys specimens are directly related to the effects of the strain rate, temperature and the evolution of the microstructural texture. The strengthening mechanism in cobalt base superalloys is the multiplication of dislocation. The dislocation density increases with increasing strain rate but decrease with increasing temperature.